 ×     #### Thank you for registering.

One of our academic counsellors will contact you within 1 working day.

Click to Chat

1800-1023-196

+91-120-4616500

CART 0

• 0

MY CART (5)

Use Coupon: CART20 and get 20% off on all online Study Material

ITEM
DETAILS
MRP
DISCOUNT
FINAL PRICE
Total Price: Rs.

There are no items in this cart.
Continue Shopping
```
Solve the following pair of linear equations by the substitution method s – t = 3 (s/3) + (t/2) = 6

```
one month ago Anand Kumar Pandey
1583 Points
```							Dear StudentGiven,s – t = 3and(s/3) + (t/2) = 6are the two equations.From 1st equation,we get,s = 3 + t ________________(1)Now, substitute the value of s in second equation to get,(3+t)/3 + (t/2) = 6⇒ (2(3+t) + 3t )/6 = 6⇒ (6+2t+3t)/6 = 6⇒ (6+5t) = 36⇒5t = 30⇒t = 6Now, substitute the value of t in equation (1)s = 3 + 6 = 9Therefore,s = 9 and t = 6.Thanks
```
one month ago
Think You Can Provide A Better Answer ?

## Other Related Questions on Algebra

View all Questions »  ### Course Features

• 731 Video Lectures
• Revision Notes
• Previous Year Papers
• Mind Map
• Study Planner
• NCERT Solutions
• Discussion Forum
• Test paper with Video Solution  ### Course Features

• 101 Video Lectures
• Revision Notes
• Test paper with Video Solution
• Mind Map
• Study Planner
• NCERT Solutions
• Discussion Forum
• Previous Year Exam Questions